2005
DOI: 10.1055/s-2004-830185
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transnasal Transsphenoidal Treatment of Pathology of the Sellar Region

Abstract: From October 2001 to the end of November 2002 in Department of Neurosurgery, Silesian University School of Medicine in Katowice 70 explorations of the sella turcica were executed using the endoscopic method. In 63 cases the operation was done because of pituitary gland adenomas. In one case the diagnosis was craniopharyngioma, in 1 chordoma of the clivus, in one glioma of the optic nerve, in 1 the reason for an operation was an empty sella syndrome and in 3 cases the pathological diagnosis was an amorphous mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 13 publications
1
49
2
6
Order By: Relevance
“…In these series, cure rates range from 57% to 100%. 7,10,13,21,22,27,31,33,34,44,57,66 We are aware of only one early study that focused specifically on outcomes after endoscopic resection in the setting of acromegaly. 44 In this early study the authors reviewed the cases of 5 patients with mostly microadenomas and reported a cure rate of 100% using a liberal cure benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…In these series, cure rates range from 57% to 100%. 7,10,13,21,22,27,31,33,34,44,57,66 We are aware of only one early study that focused specifically on outcomes after endoscopic resection in the setting of acromegaly. 44 In this early study the authors reviewed the cases of 5 patients with mostly microadenomas and reported a cure rate of 100% using a liberal cure benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…The application of endoscopes in transsphenoidal surgery in the 1990s changed this situation, because the lenses provided a wider field of view. 11,15,36,39,60 This wider view enables the surgeon to inspect the medial wall of the CS directly and therefore to pass a more reliable judgment regarding parasellar invasiveness.…”
mentioning
confidence: 99%
“…10,12,[17][18][19][20] Those that defend the bilateral approach underline the possibility of conflict between the endoscope and other surgical tools due to lack of space when the approach is done through one nostril only. [21][22][23][24]26 The bilateral transnasal endoscopic approach was used in all of the surgical procedures in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…A mechanical device is used to fixate the endoscope (a mechanical arm or holder); after the sphenoidal sinus is opened, the endoscope is fixated, leaving the neurosurgeon with both hands free to perform the procedure. 7,8,12,17,18,21,22,25,[27][28][29][30][31][32] Other authors prefer not to use an endoscope with a holder 14,15,19,20,24,26 . In the current study we did not use endoscope holders, as one of the most important advantages of the endoscope is its mobility; it can be rapidly repositioned without having to be released and refixated.…”
Section: Discussionmentioning
confidence: 99%